RANCANG BANGUN SMART PARKING PADA AREA KAMPUS BERBASIS ARDUINO MENGGUNAKAN QR CODE - Salman Farizy; Guruh Andrianto (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
Abstract The number of students using motorized vehicles which increases every year causes its own problems for a campus that has a minimal parking area, this is exacerbated by the irregular placement of vehicles which can cause damage to the vehicle, this condition can also cause other students to have difficulty finding a parking position for his vehicle. Good parking area management can help the campus to take advantage of the minimal parking area optimally, by utilizing microcontroller technology combined with QR code on student identification cards as vehicle access and website-based applications to monitor the availability of parking spaces in real time. used in this research is Research and Development (R&D) in the process of making and developing the system. With this system, besides making it easier for the campus to manage the parking area it has, it can also help students to park their vehicles properly and save the time needed to find available parking areas. Keyword---R&D, Smart Parking, QR Code, Microcontroller